Sharia, Deradicalization and National Consensus: A Review of Pancasila-inspired Philosophy as a Socio-Legal Nexus for Indonesia and Afghanistan - Muslimin, JM.; Rizapoor, Habiburrahman; Zamhari, Arif; Halid; Umar, Muhammad (International Journal of Law and Society, 2024)
This article examines the concept of Pancasila and primordial deradicalization as a socio-legal nexus for Islamic and socio-anthropological practices in Indonesia and Afghanistan, focusing on fostering a plural society. Pancasila, the philosophical foundation of the Indonesian state, has accommodated religious and cultural diversity, including legal plurality. The article explores how the principles of Pancasila can contribute to the deradicalization of extreme primordial affiliation (such as sharia) by addressing the underlying socio-anthropological factors that contribute to extremism in both countries. The study employs a comparative analysis approach, drawing on qualitative data from various sources, including academic literature. It highlights the similarities and differences in the socio-anthropological contexts of Indonesia and Afghanistan, particularly about the dynamics of Islamic values, laws, and their impact on society. By examining the role of Pancasila and its potential applicability in Afghanistan, the article aims to contribute to developing effective primordial deradicalization strategies in both countries. The findings suggest that Pancasila's emphasis on inclusivity, tolerance, and mutual respect can provide a framework for addressing the socio-anthropological factors contributing to a socio-legal nexus. The article argues that by incorporating the principles of Pancasila into deradicalization efforts, policymakers and practitioners can work towards creating a more pluralistic and cohesive society. It also explores the challenges and opportunities of implementing such an approach, considering the unique contexts of Indonesia and Afghanistan.